Evaluación de adaptación de cinco cultivares de lechuga de repollo (Lactuca Sativa L.) en el barrio San Francisco de Collanas, Salcedo, Cotopaxi. - Toapaxi Toapanta, Oscar Daniel (2023)
This research aimed to evaluate the adaptability of five cabbage lettuce cultivars provided by the Capelo seed Company, in San Francisco de Collanas neighborhood, in Salcedo canton, which has a type of sandy loam soil and pH of 7.90 in a dry temperate climate. The study varieties are GVS 29205 belonging to Golden Valley, SALINAS 3018 from Emerald Sedes, AEX 132-4090 from Apollo Sedes, IMMA from Isla Sementes, and PATAGONIA from Rijk Swaan. Four repetitions were established, giving 20 experimental units, with a total area of 345 m2; a completely randomized DBCA experimental design was used, and the Tukey test was performed at 5% to obtain statistical significance. Plant height, number of leaves, leaf length, and leaf width were measured during vegetative development, taking data at 15 days, 30 days, 45 days, and 60 days. Anthocyanin leaf coloration, main leaf vein, leaf texture, leaf shape, disease tolerance resistance, days to harvest, equatorial cabbage diameter, cabbage color, cabbage shapes, soundness, weight cabbage, and yield; these data were taken after harvest. The variety with the best results was SALINAS 3018 in the variables at 60 days, height (20.5cm), number of leaves (14), leaf length (23.4cm), leaf width (26.65cm), equatorial diameter cabbage (14.03cm), cabbage weight (601.69gr) and yield (23733kg/ha), with 67 days to be harvested, surpassing the PATAGONIA control variety. The second best variety is GVS 3018, with results at 60 days, height (18.55 cm), number of leaves (11), leaf length (21.3cm), leaf width (26.35cm), equatorial diameter of the cabbage (10.96cm), cabbage weight (488.23gr), yield (19828.3kg/ha) and with 62 days to be harvested. It was determined that SALINAS 3018 was better adapted, recommending this variety for the San Francisco de Collanas area in Salcedo canton.